STRATEGI KOLABORASI HEXAHELIX BERBASIS PEMBERDAYAAN KOMUNITAS SERIKANDI BIRU DALAM PEMANFAATAN SUMBER DAYA KABUPATEN GARUT - Hanifur Rabbani; Dwi Yuliani; Susilawati (LPPM STAI Muhammadiyah Probolinggo, 2025)
The Citra Bina Bangsa Indonesia Foundation in Garut provides community empowerment and mentoring to several communities. This is done to enable vulnerable groups in society to express their aspirations and demonstrate their capabilities within the broader social environment. This empowerment and mentoring program is intended to enable communities to thrive and adapt to all possible changes they face. Community life is shaped by a series of events and trends. To date, poverty alleviation efforts continue to seek effective solutions, one of which is empowerment programs. In its implementation, the Foundation utilizes a multi-sectoral pentahelix approach. The goal of this model is to create significant, sustainable social impact and increase community effectiveness.This research was conducted at the Citra Bina Bangsa Foundation in Garut Regency. The approach employed Participatory Action Research (PAR). The results demonstrate that Serikandi Biru successfully demonstrates how communities can become key actors in local development when supported by strong social networks and consistent cross-sector collaboration.